Estudo retrospectivo de neoplasias melanocíticas diagnosticadas no Serviço de Patologia Veterinária entre 2008 e 2023: utilização da Classificação Internacional de Doenças para Oncologia (Vet-ICD-O-Canine-1) - Teng, Fwu Shing [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Melanocytic neoplasms (melanocytoma and melanoma) originate from melanocytes in the epidermis, oral mucosa, and eyes. In the Veterinary Pathology Service of FMVZ, UNESP, Botucatu, upon reviewing the archives from 2008 to 2023, 192 (3.2%) cases of melanocytic neoplasms were diagnosed. In dogs, the prevalence, in ascending order, was melanocytoma, amelanotic melanoma, and melanoma. When evaluated in terms of location, cutaneous melanocytic neoplasms were the most prevalent (58.3%), followed by oral/mucosal ones (18.2%). A smaller percentage was diagnosed in the nasal cavity, ocular globe, and ungual bed. The most affected breeds were Mixed Breed (SRD), Dachshund (Teckel), and Miniature Pinscher. The average age was 130 months, with no difference between females and males with this type of neoplasm. Regarding the count of mitotic figures related to the type of diagnosis and location, amelanotic melanomas (21.7) showed a higher count of mitotic figures compared to melanotic melanomas (13.3).

As neoplasias melanocíticas (melanocitoma e melanoma) são originárias de melanócitos da epiderme, mucosa oral, ocular. No Serviço de Patologia Veterinária da FMVZ, Unesp, Botucatu, em revisão do arquivo, entre 2008 a 2023, foram diagnosticadas 192 (3,2%) casos de neoplasias melanocíticas. Dos exames histopatológicos, prevalência, em cães, foi em ordem crescente, melanocitoma, melanoma amelanótico e melanoma. Quando avaliado em relação à localização, neoplasias melanocíticas cutâneas foram as mais prevalentes (58,3%), seguidos das orais/mucosas (18,2%). Um menor percentual foi diagnosticado em cavidade nasal, globo ocular e leito ungueal. As raças mais acometidas foram SRD, Teckel – Daschound e Pinscher. A idade média foi de 130 meses. Não houve diferença entre fêmeas e machos com este tipo de neoplasia. Quando avaliado a contagem de figura de mitoses relacionada ao tipo de diagnóstico e localização, melanomas amelanóticos (21,7) apresentaram maior contagem de figuras de mitose comparado aos melanomas melanóticos (13,3).
Retrospective study of melanocytic neoplasms in Veterinary Pathology Service (FMVZ - UNESP, Botucatu) between 2008 and 2023: application of International Classification of Diseases for Oncology (Vet-ICD-O-Canine-1)
Keywords: Melanoma; Melanocitoma; Amelanótico